Types and Functions of Swear Words Used in Bad Santa Movie - Melan Meliyana (International Journal of English and Applied Linguistics (IJEAL), 2024)
Swearing is one of the phenomena in society that is used in conversation or dialogue in various media; one of which is the movie Bad Santa. This research is an analysis of swear words used in Bad Santa Movie. The aims of this research are to find out types of swear words and to describe the functions of swear words found in Bad Santa Movie. This research uses qualitative method. The source data is taken from the Bad Santa Movie. The writer uses Hughes’s theory in (Fauzi, 2020) to find out types of swear words and uses Anderssson and Thrudgill theory in (Sarnika, 2018) to find out its functions of swear words found in Bad Santa Movie. The result of this research shows six types of swear words and four functions from 179 data, there are: Types of swear words related to general terms 103 data, types of swear words related to name of animal 6 data, types of swear words related to religion 26 data, types of swear words related to stupidity 1 datum, types of swear words related to anatomy 25 data, types of swear words related to excretion 18 data. For the function, there are: Expletive 32 data, Abusive 22 data, Humorous 81 data, Auxiliary 44 data.